Contribution of understory species to total ecosystem aboveground and belowground biomass in temperate Pinus pinaster Ait. forests - Gonzalez, Maya; Augusto, Laurent; Gallet-Budynek, Anne; Xue, Jianming; Yauschew-Raguenes, Nathalie; Guyon, Dominique; Trichet, Pierre; Delerue, Florian; Niollet, Sylvie; Andreasson, Frida; Achat, David L.; Bakker, Mark R. (Forest ecology and management, 2013)
► We quantified the contribution of understory species to forest ecosystem biomass. ► We tested effective tools for estimating above- and belowground biomass. ► We built allometric relationships to predict biomass for five understory species. ► Understory represented about 27.4% of belowground biomass of ecosystem. ► We predicted aboveground (all species) and belowground biomass (three species). By overemphasizing the role of overstory trees in forest studies, researchers, managers and policy makers could well ignore an important functional component of the forest ecosystem: the understory. This could be particularly true in forests with relatively open canopies. In maritime pine (Pinus pinaster Ait.) plantation forests in the southwest of France, a considerable amount of the direct radiation is transmitted through the canopy and is available for the growth of understory species. This study focused on five dominant understory species, including three woody species (Calluna vulgaris L., Erica cinerea L. and Cytisus scoparius L.) and two herbaceous perennials species (Molinia caerulea L. (Moench) and Pteridium aquilinum L. Khun). For each species five pine stands with varying amounts of understory were selected to predict biomass for a wide range of values. The number of pine trees and their dimensions were recorded enabling us to estimate the aboveground and root biomass of the pines using allometric relationships. Biometrical measurements of the understory and destructive harvests were carried out in each stand to measure aboveground, coarse and fine root biomass. The results showed that the understory represented an average of 6.8% of total ecosystem aboveground biomass and 27.4% of total ecosystem root biomass, underlining the need for a broader view of this component of the forest ecosystem. Allometric relationships derived from the biometrical data enabled satisfactory predictions of aboveground biomass for all five understory species and for belowground biomass of three species (M. caerulea, P. aquilinum, C. scoparius); allometric relationships failed to predict root biomass for two woody understory species (E. cinerea and C. vulgaris).